Urodynamic profile in the Department of Urology, Cipto Mangunkusumo Hospital Between 2010 and 2015 (Faculty of Medicine Universitas Indonesia, 2019)
BACKGROUND This study was aimed to describe urodynamic profiles, the role and advantages of urodynamics for urinary problems detection, and to analyze whether urodynamic examination has been ordered based on accurate indications following guidelines in the Department of Urology Cipto Mangunkusumo Hospital between 2010 and 2015. METHODS Data was retrieved from the patientâs medical records who underwent urodynamic examinations in the Department of Urology Cipto Mangunkusumo Hospital between July 2010 to August 2015. RESULTS 1,091 patients undergone urodynamic procedures in the Department of Urology Cipto Mangunkusumo Hospital. In 553 lower urinary tract symptoms (LUTS) patients, there were 186 (34%) small bladder capacity, 84 (15%) detrusor overactivity (DO), 180 (33%) bladder outlet obstruction (BOO), and 198 (36%) bladder atony patients. In the 317 urinary retention patients, there were 121 (38%) patients with BOO and 2 (1%) patients with a normal voiding phase. In 80 overactive bladder patients, there were 51 (64%) with DO, 17 (21%) with DO incontinence, and 22 (28%) with urodynamic stress incontinence (SI). Among 81 patients with SI problems, there were 63 (78%) urodynamic SI, 9 (11%) DO, and 9 (11%) DO incontinence patients. In 60 (6%) pediatric patients, most LUTS and urinary retention patients were caused by impaired bladder contraction. CONCLUSIONS This study shows the role and superiority of urodynamics in diagnosing patients with voiding disorders, especially if with mixed components in it. Urodynamics played essential roles in detecting urinary problems at Cipto Mangunkusumo Hospital.